Survey of Emergency Physician Approaches to Management of Asymptomatic Hypertension. Issue 3 (28th September 2016) - Brody, Aaron; Twiner, Michael; Kumar, Arun; Goldberg, Elizabeth; McNaughton, Candace; Souffront, Kimberly; Millis, Scott; Levy, Phillip D.
Abstract : Uncontrolled hypertension (HTN) is commonly encountered in emergency medicine practice, but the optimal approach to management has not been delineated. The objective of this study was to define emergency physician (EP) approaches to management of asymptomatic HTN in various clinical scenarios and assess adherence to the American College of Emergency Physician clinical policies, utilizing an online survey of EPs. A total of 1200 surveys were distributed by e‐mail with completion by 199 participants. The variables associated with a decision to prescribe oral antihypertensive medications were a history of HTN and referral from primary care. Acute blood pressure (BP) reduction using intravenous antihypertensive medications was also more likely with the latter and BP >180/120 mm Hg. Logistic regression revealed association of EP female sex, fewer years in practice, and a high‐volume practice setting with guideline‐concordant therapy. Wide variability exists in EP approaches to patients with asymptomatic HTN. Treatment decisions were impacted by patient history of chronic HTN, referral from primary care providers, and magnitude of BP elevation.